A review on equivalence‐based procedures to teach food‐portion estimation skills. (12th February 2023) - Díaz, Melissa; Garcia, Yors; Mahoney, Amanda
Abstract: This review involved a systematic analysis of equivalence‐based instruction (EBI) that aimed to improve food‐size interventions in diverse populations. Systematic searches identified seven studies published since 2010 that met inclusion criteria. These studies were analyzed according to their participants, design, setting, content taught, training structures, training protocol, testing format, treatment integrity, and outcomes. Results showed EBI procedures for teaching food estimation skills have been mostly implemented with adults. The type of content taught in the identified studies included carbohydrate ranges, portion size with food and non‐food items, measuring cups and nutritional content of calories. Majority of included studies used one‐to‐many training structure and simultaneous protocols for teaching stimulus relations. Five studies completed a generalization probe and three studies reported treatment integrity data. Overall, all participants demonstrated skill acquisition of novel relations between food and portion measurement aides. Recommendations for future research and clinical applications of EBI in teaching food portion estimation are presented.